Kajian Teoritis Immune Trombositopenia pada Anak: Aspek Klinis, Prognosis, dan Pendekatan Terapi - Debita Syahira; Elli Kusmayanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Immune Thrombocytopenic Purpura (ITP) is a bleeding disorder characterized by a low platelet count (<100,000/µL) caused by decreased platelet production or opsonization by antibodies, leading to platelet destruction by the reticuloendothelial system. ITP is one of the most common etiologies of bleeding disorders, especially in children. The prevalence of ITP in children is estimated to be around 1.9 to 6.4 cases per 100,000 children annually, while in adults, the prevalence is lower, at about 3.3 cases per 100,000 people per year. In the United States, the incidence of ITP is reported to be around 1.6 per 10,000 people annually. Clinical manifestations of ITP include petechiae, purpura, and/or ecchymosis, which are usually found on the upper and lower extremities. Mucocutaneous bleeding symptoms such as epistaxis and gum bleeding are also common in patients. These symptoms can vary depending on the severity of thrombocytopenia and individual responses to the condition. Diagnosis of ITP is made through a thorough medical history, physical examination, and rapid supportive tests to confirm the diagnosis and differentiate ITP from other conditions with similar symptoms. Proper and timely management is crucial to prevent further complications, including more severe bleeding or organ damage. With effective management, the quality of life of patients can be improved, and the risks associated with ITP can be minimized. Therefore, early detection and optimal management are key in addressing ITP, particularly in children who are more vulnerable to this bleeding disorder.